Analisis Perencanaan Laba Melalui Perhitungan Break Even Point (BEP) Pada Usaha Kerajinan Tangan Pembuatan Rumah Honai Kelurahan Klasaman Kota Sorong Papua Barat Daya - Kbarek, Eugenia; Yable, Welly Salomi; Sipayung, Victor S.; Hamdika, Ghazali; Rewetwa, Elsa Febrianti; Muskita, Susana Magdalena Welly (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This research aims to provide information to the public regarding the definition, use, purpose and calculation method of Break Even Point (BEP) analysis both in units and rupiahs in the sale of Handicraft Products for Making Honai Houses, Klasaman Village, Sorong City, Southwest Papua. By knowing the break-even point, we can determine the amount of expenses and income according to the target we want to achieve. The location of this research is located in Klasaman Village, Sorong City, Southwest Papua. The location was chosen because of its role as a trading center. This study uses statistical analysis to process sales data and calculate BEP. This study uses a quantitative descriptive method. The results of this study show that the calculation of BEP in the sales unit of Handicraft Products for Honai House Making, Klasaman Village, Sorong City, Southwest Papua. In July 2024, the break-even point is at 4.82 units with a sales level of Rp. 1,204,238.92 and during July 20 units are sold, the revenue is Rp. 5,000,000, then the profit level is Rp. 2,364,000. Then the profit planning in August 2024, shows an increase in sales capacity to 30 units with gross revenue of Rp. 7,500,000, profit obtained is Rp. 4,046,000. The break-even point was at 4.69 units with sales of Rp. 1,172,791.24. The results of this study show that profit planning has increased in August.